Capillary forces exerted by a water bridge on cellulose nanocrystals: the effect of an external electric field. Issue 8 (13th February 2023) - Karna, Nabin Kumar; Wohlert, Jakob; Hjorth, Anna; Theliander, Hans
Abstract : Capillary forces between cellulose channels depend on the direction and magnitude of an applied electric field. An electric field applied parallel to a solid–liquid interface increases the capillary force while a perpendicular field reduces it. Abstract : Capillary forces play an important role during the dewatering and drying of nanocellulosic materials. Traditional moisture removal techniques, such as heating, have been proved to be deterimental to the properties of these materials and hence, there is a need to develop novel dewatering techniques without affecting the desired properties of materials. It is, therefore, important to explore novel methods for dewatering these high-added-value materials without negatively influencing their properties. In this context, we explore the effect of electric field on the capillary forces developed by a liquid–water bridge between two cellulosic surfaces, which may be formed during the water removal process following its displacement from the interfibrillar spaces. All-atom molecular dynamics (MD) simulations have been used to study the influence of an externally applied electric field on the capillary force exerted by a water bridge. Our results suggest that the equilibrium contact angle of water and the capillary force exerted by the water bridge between two nanocellulosic surfaces depend on the magnitude and direction of the externally applied electric fields. Hence, an external electric field can be applied to manipulate the capillary forces between two particles. The close agreement between the capillary forces measured through MD simulations and those calculated through classical equations indicates that, within the range of the electric field applied in this study, Young–Laplace equations can be safely employed to predict the capillary forces between two particles. The present study provides insights into the use of electric fields for drying of nanocellulosic materials.